2021
DOI: 10.1002/oby.23161
|View full text |Cite
|
Sign up to set email alerts
|

The Triple Health Threat of Diabetes, Obesity, and Cancer—Epidemiology, Disparities, Mechanisms, and Interventions

Abstract: Obesity and type 2 diabetes are both chronic, relapsing, progressive diseases that are recognized as risk factors for the development of multiple types of cancer. In a recent symposium titled “Hitting A Triple—Diabetes, Obesity, and the Emerging Links to Cancer Risk,” convened by The Obesity Society during ObesityWeek 2019, experts in the field presented the current science and highlighted existing research gaps. Topics included (1) the epidemiology of obesity and diabetes and their links to cancer risk; (2) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 102 publications
(106 reference statements)
0
10
0
1
Order By: Relevance
“…There are known shortcomings of using BMI as an indicator of obesity in cancer research, with several reviews highlighting the inability of BMI to accurately characterize body composition across races. 42,68,69 The Carolina Breast Cancer Study found that waist-hip ratio was associated with breast cancer incidence in both White and Black women, whereas there was no risk associated with BMI. 70 Unfortunately, other measures of body composition are often not as readily available as BMI, especially in EHR-derived data.…”
Section: Discussionmentioning
confidence: 99%
“…There are known shortcomings of using BMI as an indicator of obesity in cancer research, with several reviews highlighting the inability of BMI to accurately characterize body composition across races. 42,68,69 The Carolina Breast Cancer Study found that waist-hip ratio was associated with breast cancer incidence in both White and Black women, whereas there was no risk associated with BMI. 70 Unfortunately, other measures of body composition are often not as readily available as BMI, especially in EHR-derived data.…”
Section: Discussionmentioning
confidence: 99%
“…The global epidemics of obesity and type 2 diabetes mellitus (T2DM) are major public health concerns [ 1 ]. These overnutrition-related chronic diseases are associated with changes in diet and physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…The substantially higher rate of uterine cancer amongst those with diabetes is a reminder of the importance of addressing obesity (i.e. a shared risk factor) in reducing the occurrence of both Type-2 diabetes and obesity-related cancer, including uterine, breast and steatohepatitic liver cancer [ 43 , 44 ]. It must be noted that the current study is not able to disentangle whether the increased risk of some cancers among those with diabetes is a direct consequence of their diabetes, or their diabetes is a direct consequence of their cancer, or due to some other reason.…”
Section: Discussionmentioning
confidence: 99%